Tracing absolute lymphocytosis to T-large granular lymphocytic leukaemia in elderly: a flowcytometry based case report - Hidangmayum, Abena; Chandrasekhar, Beena; Sai Jaine, Nagarjun; Singh Mehra, Kailash; Prasad Joshi, Ravindra (International Journal of Research in Medical Sciences, 2025)
T-cell large granular lymphocytic leukaemia (T-LGL leukaemia) is a rare, neoplastic proliferation of cytotoxic T cells, accounting for less than 5% of all chronic lymphoproliferative disease. Diagnosing T-LGLL can be challenging, particularly in distinguishing it from reactive lymphocytosis. Despite its indolent nature, T-LGL leukaemia remains incurable, highlighting the need for improved therapeutic strategies. The TRBC1 flow cytometric assay provides a rapid and reliable means of assessing T-cell clonality in patients with large granular lymphocytosis, facilitating diagnosis through detection of altered proportions of TRBC1⁺ αβ T cells. We report a case of T-LGL leukaemia with an immunophenotypic clonal T-cell, characterised as a CD4-/CD8+ T-cell, TCRαβ subset, exhibiting downregulation of CD5 and CD7, with expression of the NK Cell marker CD16.